Kinetic Evidence of an Apparent Negative Activation Enthalpy in an Organocatalytic Process - Han, Xiao; Lee, Richmond; Chen, Tao; Luo, Jie; Lu, Yixin; Huang, Kuo-Wei (Scientific reports, 2013)
A combined kinetic and computational study on our tryptophan-based bifunctional thiourea catalyzed asymmetric Mannich reactions reveals an apparent negative activation enthalpy. The formation of the pre-transition state complex has been unambiguously confirmed and these observations provide an experimental support for the formation of multiple hydrogen bonding network between the substrates and the catalyst. Such interactions allow the creation of a binding cavity, a key factor to install high enantioselectivity.